Effects of simultaneous use of m-NMES and language training on brain functional connectivity in stroke patients with aphasia: A randomized controlled clinical trial - Xie, Hui; Jing, Jing; Ma, Yanping; Song, Ying; Yin, Jiahui; Xu, Gongcheng; Li, Xinglou; Li, Zengyong; Wang, Yonghui (Frontiers in Aging Neuroscience, 2022)
Introduction The m-NMES had been demonstrated to redistribute brain resources and induce plastic changes in the stroke patients. However, the physiological mechanism and clinical efficacy of m-NMES combination with existing clinical rehabilitation programs remains unclear in patients with aphasia after stroke. This study aimed to investigate the effects of simultaneous use of m-NMES and language training (m-NMES-LT) with on cerebral oscillations and brain connection, as well as the effect on clinical efficacy. Materials and methods Total 21 right–handed adult patients with aphasia were randomly assigned to language training (LT) group and m-NMES-LT group, and tissue concentration of oxyhemoglobin and deoxyhemoglobin oscillations were measured by functional near-infrared spectroscopy in resting and treatment state during three consecutive weeks. Five characteristic frequency signals (I, 0.6–2 Hz; II, 0.145–0.6 Hz; III, 0.052–0.145 Hz; IV, 0.021–0.052 Hz; and V, 0.0095–0.021 Hz) were identified using the wavelet method. The wavelet amplitude (WA) and wavelet phase coherence (WPCO) were calculated to describe the frequency-specific cortical activities. Results The m-NMES-LT induced significantly higher WA values in contralesional PFC in intervals I, II, and V, and ipsilesional MC in intervals I-V than the resting state. The WPCO values between ipsilesional PFC-MC in interval III-IV, and between bilateral MC in interval III-IV were significantly higher than resting state. In addition, there was a significant positive correlation between WPCO and Western Aphasia Battery in m-NMES-LT group. Conclusion The language training combined with neuromuscular electrical stimulation on median nerve could improve and achieve higher clinical efficacy for aphasia. This is attributed to the m-NMES-LT could enhance cortical activation and brain functional connectivity in patients with aphasia, which was derived from myogenic, neurogenic, and endothelial cell metabolic activities.